PENGARUH PENDAPATAN TERHADAP POLA BERWISATA MASYARAKAT PERKOTAAN (STUDI KASUS MASYARAKAT KOTA BOGOR) - Asep Parantika; Putu Rifzki Azhari (Majalah Ilmiah Widyacakra, 2020)
ABSTRACTIndonesian big cities are rapidly developing in many aspects, making them very busy cities.In big cities, people are so busy working that the author became concerned to find outwhether the people have enough vacation or not. Working causes stress, and too much stressis not good for health, so people in busy cities like Bogor need to go on a vacation now andthen to reduce their stress level. According to Central Bureau of Statistics Bogor, Bogor isnow early Metropolis, because the recorded population of Bogor in 2018 was 1.1 million.According to cencus of 2010, 2016, and 2017, the population of Bogor has been constantlyrising. So it is safe to assume that in 2018 the number is above 1.100.000, since there was nosignificant event that could have led to a significant reduction of the population. The authorsurveyed a sample from the population of Bogor people and analyze the data gathered fromthe survey to find correlation between the income and tourism pattern of the people of Bogor.Using the method of Pearson Product Moment, it is found that income correlates withtourism pattern with a score of 0,44 which classifies as medium correlation. It is also foundthat the determination coeficient of the two variables is 19,36% which means that 19, 36%factor that affects tourism pattern is income, meanwhile the rest 80,64% is from factors thatthe author didn’t research. Other than finding the correlation between income and tourismpattern, the author also studied into the tourism pattern of the people, the author has foundthat most Bogor citizen mostly prefer to go to natural attractions and with their families.This research is expected to be able to contribute to the awareness of the importance ofvacation and to improve the understanding of the government and the people toward theeffects on financial condition to tourism pattern. It is also expected that this research couldbe used as a reference for future research.